Renaissances the one or the many? - Goody, Jack
"One of the most distinguished social scientists in the world addresses one of the central historical questions of the past millennium: does the European Renaissance deserve its unique status at the very heart of our notions of modernity? Jack Goody scrutinizes the European model in relation to parallel renaissances that have taken place in other cultural areas, primarily Islam and China, and emphasizes what Europe owed to non-European influences. Renaissances continues that strand of historical analysis critical of Eurocentrism that Goody has developed in recent works like The East in the West (1996) or The Theft of History (2007). This book will be of interest to students of the Renaissance and of the history of western civilization more generally, to anthropologists, sociologists and all those with an interest in the construction of modernity."--BOOK JACKET.